Histomicrobiologic aspects of the root canal system and periapical lesions in dogs' teeth after rotary instrumentation and intracanal dressing with Ca(OH)2 pastes - Soares, Janir Alves; Leonardo, Mário Roberto [UNESP]; Da Silva, Léa Assed Bezerra; Tanomaru Filho, Mario [UNESP]; Ito, Izabel Yoko (FapUNIFESP (SciELO), 2006)
OBJECTIVE: The purpose of this study was to evaluate the distribution of microorganisms in the root canal system (RCS) and periapical lesions of dogs' teeth after rotary instrumentation and placement of different calcium hydroxide [Ca(OH)2]-based intracanal dressings. MATERIALS AND METHODS: Chronic periapical lesions were experimentally induced in 80 premolar roots of four dogs. Instrumentation was undertaken using the ProFile rotary system and irrigation with 5.25% sodium hypochlorite. The following Ca(OH) 2-based pastes were applied for 21 days: group 1 - Calen (n=18); group 2 - Calen+CPMC (n=20); group 3 - Ca(OH)2 p.a. + anaesthetic solution (n=16) and group 4 - Ca(OH)2 p.a.+ 2% chlorhexidine digluconate (n=18). Eight root canals without endodontic treatment constituted the control group. Histological sections were obtained and stained with Brown & Brenn staining technique to evaluate the presence of microorganisms in the main root canal, ramifications of the apical delta and secondary canals, apical cementoplasts, dentinal tubules, areas of cemental resorption and periapical lesions. The results were analyzed statistically by the Mann-Whitney U test (p<0.05). RESULTS: The control group showed the highest prevalence of microorganisms in all sites evaluated. Gram-positive cocci, bacilli and filaments were the most frequent morphotypes. Similar microbial distribution patterns in the RCS and areas of cementum resorption were observed in all groups (p>0.05). The percentage of RCS sites containing microorganisms in groups 1, 2, 3, 4 and control were: 67.6%, 62.5%, 78.2%, 62.0% and 87.6%, respectively. CONCLUSION: In conclusion, the histomicrobiological analysis showed that the rotary instrumentation and the different calcium hydroxide pastes employed did not effectively eliminate the infection from the RCS and periapical lesions. However, several bacteria seen in the histological sections were probably dead or were inactivated by the biomechanical preparation and calcium hydroxide-based intracanal dressing.
Keywords: Calcium hydroxide pastes; Endodontic infection; Periapical lesions; Root canal therapy